Tourism and Livable Towns Beyond the Coronavirus Disease 2019: A Case Study for Chongqing, China - Ke Su; Ke Su; Chao Zhou (Frontiers Media S.A., 2020)
Based on the data of 812 small towns in Chongqing, China, this paper attempts to conduct an empirical analysis on whether tourist towns with excellent natural environment, policy advantage, and market preference are more ecologically livable than ordinary small towns. It is found that as a whole, tourist towns are indeed more ecologically livable than ordinary small towns. Also, from the perspective of grading, both the national and provincial tourist towns have the advantage of ecological livability, but the advantage of national ones is more prominent. Furthermore, the ecological livability of tourist towns is affected by location advantage and policy inclination. The implications of the results are discussed following the outcomes of the coronavirus disease 2019 outbreak. The suggestions beyond the coronavirus disease 2019 are also provided.